The “Systems Rationality” of Financial Capital - Smith, Tony (Radical Philosophy Review, 2019)
Philosophy
Keywords: KONINGS; Martijn; book review; critique

Karl Polanyi. El Racionalismo Económico Como Motor De La Utopía Liberal - Goikoetxea Berdonces, Maialen (KARL POLANYI. THE ECONOMIC RATIONALISM AS THE MOTOR OF THE LIBERAL UTOPIA., 2018)
Karl Polanyi's main thesis is the effective separation of society and economy, placing the economy above the society. This artificial separation will be carried out by a series of theoretical tools and mechanisms -the introduction of fictitious goods and economic rationalism as a social premise- that will blind an overall view of the social panorama, focusing only on the economic aspects of it, causing that way, an unprecedented human crisis. (English)
Political Science; Philosophy
Keywords: capitalism; capitalismo; economic rationalism; fictitious goods; liberal utopia; mercancías ficticias; racionalismo económico; utopía liberal

The Double Movement in Polanyi and Hayek: Towards the Continuation of Life - Faria, Filipe Nobre (Ethics, Politics & Society, 2018)
Karl Polanyi’s double movement is a dialectical process characterized by a continuous tension between a movement towards social marketization and a movement towards social protectionism. Notably, Polanyi condemns the former movement while defending the latter. Without using the term “double movement”, F.A Hayek’s theory of social evolution acknowledges the same phenomenon but reaches different normative conclusions. While for Polanyi the marketization of society is a utopia with dystopian consequences, Hayek’s evolutionary explanation of this dialectical process asserts that there is no alternative to a market oriented society. Both authors defend that their favoured movement is the one that truly supports the continuity of life. This article compares the authors’ normative readings of the double movement and concludes that, from an evolutionary perspective, Polanyi’s conclusion possesses a robustness that Hayek’s postulate lacks.
Philosophy
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; double movement

Capitalism: A Conversation in Critical Theory - Fraser, Nancy; Jaeggi, Rahel (John Wiley & Sons, 2018)
In this important new book, Nancy Fraser and Rahel Jaeggi take a fresh look at the big questions surrounding the peculiar social form known as “capitalism,” upending many of our commonly held assumptions about what capitalism is and how to subject it to critique. They show how, throughout its history, various regimes of capitalism have relied on a series of institutional separations between economy and polity, production and social reproduction, and human and non-human nature, periodically readjusting the boundaries between these domains in response to crises and upheavals. They consider how these “boundary struggles” offer a key to understanding capitalism’s contradictions and the multiple forms of conflict to which it gives rise. What emerges is a renewed crisis critique of capitalism which puts our present conjuncture into broader perspective, along with sharp diagnoses of the recent resurgence of right-wing populism and what would be required of a viable Left alternative. This major new book by two leading critical theorists will be of great interest to anyone concerned with the nature and future of capitalism and with the key questions of progressive politics today.
Philosophy; Political Science
Keywords: boundary struggle; capitalism; political philosophy; triple movement

Mercados, historia y teleología: reflexiones desde la noción de «doble movimiento» de Karl Polanyi - Polo Blanco, Jorge Polo (CONVIVIUM, 2018)
En el presente trabajo mostraremos que la filosofía liberal operó en muchas ocasionesa través de un esquema teleológico, desde el cual entendía que la espontaneidad delmovimiento histórico conducía de forma natural hacia una economía de mercados libres.Semejante interpretación tenía que presuponer otra controvertida tesis, a saber, que lascategorías que informan la racionalidad práctica dentro de una sociedad de mercado no sonuna simple contingencia histórica, sino que responden a la estructura lógica de cualquieracción humana; esto es, como si toda acción humana, en cualquier tiempo y lugar, hubiesefuncionado a través de una misma lógica inmutable que coincidía, en lo esencial, con laracionalidad típica de una economía de mercado. Para adentrarnos críticamente en estaproblemática utilizaremos la obra de Karl Polanyi, cuya obra se oponía frontalmente a estasdos tesis manejadas por el liberalismo económico.
Philosophy; Economics
Keywords: MISES; Ludwig von; doble movimiento; double movement; economía de mercado; historical teleology; market economy; teleología histórica

Karl Polanyi in Dialogue: A Socialist Thinker for our Times - Brie, Michael (Black Rose Books, 2017)
Featuring essays from Michael Brie (Rose Luxemburg Foundation, Berlin), Nancy Fraser (New School for Social Research, New York) and Kari Polanyi-Levitt (McGill University, Montreal). The contemporary Left fights its political battles on various fronts: protesting the crippling structural inequalities that sustain neoliberal economic policy; developing sustainable, community-based alternatives to the consumerism and short-termism that exacerbate the environmental crisis; and advocating for the cultural recognition, emancipation and celebration of the diversity and pluralism of human identity. But despite this versatility the Left appears to be in worldwide retreat whilst an aggressive new ‘Alt-Right’ is taking to the internet and the streets, regurgitating a regressive and patriarchal vision of society that has already won startling political victories in the US and Europe. Amidst the vertiginous tension of such a crisis, Michael Brie argues for an urgent theoretical and practical reorganisation of the Left. Developing the work of philosopher and social theorist Karl Polanyi, Brie advocates an alliance of socialist liberals and libertarian ‘commonists’ that unites contemporary campaigns for recognition, difference and human dignity with more traditional struggles for social welfare and economic democracy. Starting with Nancy Fraser’s critical reappraisal of Polanyi in her article “A Triple Movement? Parsing the Politics of Crisis after Polanyi” (included), Brie powerfully reinterprets Polanyi’s thought for present times, developing concrete proposals for a Polanyian political response to neoliberalism, an ascendent authoritarian right and the ongoing threat of global ecological disaster. Also included are two articles by Polanyi translated into English for the first time and Kari Polanyi-Levitt’s lecture at the Rosa Luxemburg Foundation “From the Great Transformation to the Great Financialisation”.
Philosophy; Political Science
Keywords: biography; ecology; economics; feminism; history; labor; labour; politics; racism; sociology

Nancy Fraser and Karl Polanyi. A Possible Dialogue - Brie, Michael (Karl Polanyi in Dialogue: A Socialist Thinker for our Times, 2017)
From the very beginning a misunderstanding has to be cleared up – the reduction of Polanyi’s work to that of a reformer who wants to counter the excesses of market radicalism with social protective measures and believes that the crisis of modern
Philosophy
Keywords: FRASER; Nancy; triple movement

The catastrophe of neo-liberalism Finance, emancipation and disintegration - Foster, Roger (Philosophy & Social Criticism, 2016)
My article provides a systematic interpretation of the transformation of capitalist society in the neo-liberal era as a form of what Karl Polanyi called ‘cultural catastrophe’. I substantiate this claim by drawing upon Erich Fromm’s theory of social character. Fromm’s notion of social character, I argue, offers a plausible, psychodynamic explanation of the processes of social change and the eventual class composition of neo-liberal society. I argue, further, that Fromm allows us to understand the psychosocial basis of the process that Polanyi calls cultural catastrophe. This requires an elucidation of the major social forces of financialization and emancipation which, I argue, proved to be important formative factors in the emergence of neo-liberal society. The cultural catastrophe of neo-liberalism concerns the working class, whose prevailing social character has become misaligned with the new expectations and requirements of neo-liberal society.
Philosophy
Keywords: FROMM; Erich; cultural catastrophe; emancipation; financialization; neo-liberalism; neoliberalism

État social, démocratie et construction européenne. Pour une citoyenneté sociale européenne - Delruelle, Édouard (Revue Française d'Histoire des Idées Politiques, 2016)
L’idée de « modèle social européen » n’est-elle qu’un leurre ou un objectif politique que les forces progressistes doivent continuer à promouvoir ? L’article s’interroge sur les fondements proprement philosophiques (souvent négligés) de l’État social – à la fois système assurantiel universel et institution d’un « citoyenneté sociale » (T.H. Marshall), dont la dynamique excède la forme de l’Etat-nation., Is the idea of a “European social model” but a decoy or is it a political aim that progressive forces need to keep on promote? This paper is concerned with the (often neglected) philosophical foundations of the welfare state – both a universal insurance system and the establishment of a “social citizenship” (T.H. Marshall) whose dynamics extend beyond the form of the nation-state.
Philosophy
Keywords: social citizenship; welfare state

Europe at a Crossroads: Failed Ideas, Fictional Facts, and Fatal Consequences - Thomasberger, Claus (Forum for Social Economics, 2015)
The crisis of the European Monetary Union has revealed the weakness and the fragility of the European integration process. The paper examines the institutional changes which are at the root of the instability. What are the driving forces behind the introduction of the euro? What role do theoretical considerations play in this process? What influence on European integration has been exerted by neoliberal beliefs and convictions? Relying on an approach that combines basic insights of Gunnar Myrdal with Karl Polanyi's idea of a "double movement," it concentrates on the institutional transformation that is at the basis of the European integration process. The relationship between (misleading) ideas and facts is at the center of the study. It examines the influence of ideas and theoretical models on European integration, the Single Market Program, the Maastricht process, the increasing imbalances since the introduction of the euro, and the strategies applied during the recent crisis.
Economics; Philosophy
Keywords: economic integration; financial aspects of economic integration; financial crises; international institutional arrangements

Żeby sprzedać – trzeba dać O rynku i jego nierynkowych fundamentach - Michalski, Michał A. (Prakseologia, 2015)
The paper analyzes interdependence of the market sphere which functions according to the logic of contract, and the sphere of non-market activity within economy, where the logic of gift dominates as a paradigm. The purpose of the analysis is to present how the above concepts of societal exchange intertwine and complete each other within the socio-economic order. This is followed by the description of 'pre-market' economic paradigms (based on Karl Polanyi's contribution) such as reciprocity, redistribution and household. Special attention is paid to category of gift, which is presented as prior to contract and being a necessary condition of the former one. The purpose of the analysis undertaken in this paper is to show how understanding of the interaction discussed here is necessary for creating integrated vision of how socio-economic order functions and offers adequate perspective for formulating recommendations within social and economic policy. (English) "To Sell One Has to Give – of Market and Its Non-Market Foundations"
Sociology; Philosophy
Keywords: contract; economy; gift; gospodarka; kontrakt; market; rynek; socio-economic order; ład społeczno-gospodarczy

Toward a Sartrean Economics - Kail, Michel; Sobel, Richard (Rethinking Marxism, 2015)
Despite the absence of a systematic analysis of economics in Sartre's work, we argue that a Sartrean economics can indeed be said to exist, even if it is an economics that still awaits development. The status that Sartre accords to the concept of scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason but should be considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man's confrontation with a typically ungrateful nature but should rather be articulated through the concept of the world as elaborated in Sartrean philosophy.
Political Science; Philosophy
Keywords: POLANYI; Karl; 1886-1964; SARTRE; Jean-Paul; 1905-1980; economic systems; economism; scarcity; world

Le religioni della politica: Fra democrazie e totalitarismi - Gentile, Emilio (Gius.Laterza & Figli Spa, 2014)
La sacralizzazione della politica accade ogni volta che un'entità politica – la nazione, la democrazia, lo Stato, la razza, la classe, il partito, il movimento – è trasformata in una entità sacra, in un oggetto di devozione e di culto, ed è collocata al centro di un sistema di credenze, di simboli e di riti. Nascono allora le religioni della politica, che non si identificano con un unico tipo di ideologia e di regime: esse possono sacralizzare la democrazia o l'autocrazia, l'eguaglianza o la disuguaglianza, la nazione o l'umanità.
Philosophy
Keywords: essence of fascism; fascism; history / modern / 21st Century; political philosophy

The Passage West: Philosophy After the Age of the Nation State - Marramao, Giacomo (Verso Books, 2014)
In this ambitious work, Giacomo Marramao proposes a radical reconceptualization of the world system in our era of declining state sovereignty. He argues that globalization cannot be reduced to mere economics or summarized by phrases such as ‘the end of history’ or the ‘westernization of the world’. Instead, we find ourselves embarking on a passage to a new, post-nation state age destined to transform all civilizations – and to disrupt Western geopolitical dominance. To confront the challenges of this interregnum one must think in terms of a new and radical universalism, a universalism of difference able to revitalize politics and to demythologize identity.Building on the great interwar discussion between Spengler, Junger, Schmitt and Heidegger, Marramao’s new work engages with Habermas, Derrida and post-colonialism. Arguing against the classic Western pretension to universal norms of democracy and reason, he develops instead the idea of a ‘universal politics of difference’. KM - contains chapter: Gift, exchange, obligation: Karl Polanyi and social philosophy
Philosophy; Political Science
Keywords: exchange; international relations; religious philosophy; social philosophy

Fortunes of Feminism: From State-Managed Capitalism to Neoliberal Crisis - Fraser, Nancy (Verso Books, 2013)
Charts the history of women’s liberation and calls for a revitalized feminism.Nancy Fraser’s major new book traces the feminist movement’s evolution since the 1970s and anticipates a new—radical and egalitarian—phase of feminist thought and action.During the ferment of the New Left, “Second Wave” feminism emerged as a struggle for women’s liberation and took its place alongside other radical movements that were questioning core features of capitalist society. But feminism’s subsequent immersion in identity politics coincided with a decline in its utopian energies and the rise of neoliberalism. Now, foreseeing a revival in the movement, Fraser argues for a reinvigorated feminist radicalism able to address the global economic crisis. Feminism can be a force working in concert with other egalitarian movements in the struggle to bring the economy under democratic control, while building on the visionary potential of the earlier waves of women’s liberation. This powerful new account is set to become a landmark of feminist thought.
Philosophy; Political Science
Keywords: critical theory; feminism; feminist theory; triple movement

A Triple Movement? - Fraser, Nancy (New Left Review, 2013)
Philosophy; Political Science
Keywords: double movement; social protection; triple movement

Polanyi and Hayek on Freedom, the State, and Economics - Filip, Birsen (International Journal of Political Economy, 2012)
This paper examines the relationship that prevails between the state, economics, and freedom according to the works of Friedrich Hayek and Karl Polanyi. Hayek, who was one of the most important contributors to the development of the modern market economy and liberalism, formulated a concept of freedom that includes economic and negative freedom as significant components; his objective was to demonstrate the superiority of liberal capitalist societies over all other forms of organizing a society in terms of achieving freedom. Meanwhile, Polanyi, who confronted all forms of totalitarian regimes and argued that a "self-regulating market … was a utopian project," formulated a concept of freedom that rejected the self-regulating mechanism of the market economy as a component of freedom; he supported regulated markets and included moral, ethical, and social values among the key components required for the realization of freedom. This paper shows that Hayek failed to foresee the destructive social consequences and dehumanizing aspects of modern market capitalism, and promoted the free market economy as a guardian of freedom primarily for its instrumental value. Conversely, Polanyi was able to anticipate the modern market economy's potential to engender disastrous consequences for the whole of humanity and provided an honest and objective analysis of the modern market system that is indispensable for understanding the dilemmas, issues, and contradictions of economic globalization.
Philosophy
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; capitalism; economics; globalization; modern market economy; negative freedom; open society; political philosophy; positive freedom

The Embedded Market and Ideology Critique - Johnson, Pauline (Critical Horizons, 2011)
The article examines the ideology critical potentials of the concept of the embedded market, made famous by philosopher and economic historian Karl Polanyi. It explores several readings of this concept and assesses their ability to revive critical powers of sociology. It discusses the book "The New Spirit of Capitalism," by Luc Boltanski and Eve Chiapello, as a specific take on such an idea. It also offers a re-examination of Polanyi's interpretations of the embedded markets thesis.
Sociology; Philosophy
Keywords: Boltanski and Chiapello; embedded markets; ideology; neoliberalism; philosophers; philosophy; social theory; sociology

The second great transformation: Towards a solidarity society - Brie, Michael; Klein, Dieter (International Critical Thought, 2011)
The double transition to a society based on unfettered capital valorisation, which attempts to legitimize itself by claiming to be a democratic society founded on human rights, can be defined as the first great transformation of the contemporary period. These bourgeois capitalist societies are now in a crisis of their reproduction, integration, rule and security. Three possible scenarios can be discerned: the first attempts to continue the present development (conventional world), the second, the formation of authoritarian fortresses in the centres within an ocean of insecurity and degradation, or, the third, a new transformation to a solidaristic social development. This transformation would begin in capitalism and at the same time point beyond it to a society whose most important goal is the development of free individuals through solidarity-based associations in the economy, in politics and in culture. Its basis would be a solidarity-based multi-sector economy and a participatory democracy. Although the totality of a new society cannot be anticipated, concrete entry projects for a new second transformation can be developed.
Philosophy; Political Science
Keywords: capitalism; double transformation; socialism; solidarity economy

Marketization, social protection and emancipation: ambivalences of feminism in the capitalist crisis - Fraser, Nancy (Revista Direito GV, 2011)
This article is a reflection on the perspectives of feminism in the context of the current crisis of neoliberal capitalism. It is based on the theories of Karl Polanyi that explained the historical process of the crises as a result of the conflict between two elements – marketization and social protection. However, Polanyi Kept out of sight forms of injustice that are not present in the market. He also had the tendency to excuse the social protection as an instrument of domination. This article takes a broader view on the analysis of the conflict between Marketization and social protection. It includes in the analysis a third dimension, the emancipation. The inclusion of this third element transforms the historical process in a three dimensional conflict and forms the heart of a quasi-polanyian perspective that is able to explain the crisis of the XXI century. This text develops this new perspective and uses it to analyze the bets in the emancipation of the gender hierarchy. The triple movement, thus constituted, can overcome the ambivalence of feminism, as the feminist agenda was often manipulated by neoliberalism. The redefinition of social protection in democratic, participatory, non-hierarchic and non-oppressive terms, opens the possibility to a new feminist politics. Keywords: Capitalism; Emancipation; Welfare State; Feminism; Gender.
Philosophy; Political Science
Keywords: capitalism; emancipation; feminism; gender; welfare state

Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Philosophy; Political Science
Keywords: capitalism; emancipation; feminism; gender; welfare state

Y a-t-il une économie sartrienne ? - Kail, Michel; Sobel, Richard (L'Homme & la société, 2011)
RésuméEn dépit de l’absence d’un exposé économique systématique dans l’œuvre de Sartre, nous soutenons qu’il y a bien une économie sartrienne, même si celle-ci est encore à développer. Le statut que Sartre réserve à la « rareté » lui permet de faire un pas supplémentaire vers la critique de l’économisme par rapport à celui déjà effectué par Karl Polanyi, qui s’est contenté de récuser la confusion entretenue entre l’économique et sa définition formelle. La rareté, nous enseigne Sartre, ne saurait en effet être soumise au traitement de la raison instrumentale, mais considérée, ajoute-t-il, comme un fait humain dans l’histoire. Aussi, l’analyse économique ne doit-elle pas s’appuyer sur la notion de « nature » et la thématique de l’homme confronté à la nature, en l’occurrence « ingrate », mais articulée sur la notion de « monde » telle que la philosophie sartrienne l’élabore., Despite the absence of a systematic analysis of economics in Sartre’s work, we argue that there can indeed be said to be a Sartrean economics, even if it is one that still awaits development. The status which Sartre accords to the concept of Scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason, but considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man’s confrontation with a typically ungrateful Nature, but articulated through the concept of World as elaborated in Sartrean philosophy.
Political Science; Philosophy
Keywords: SARTRE; Jean-Paul; 1905-1980; economic systems

Five Theses on the Common - Roggero, Gigi (Rethinking Marxism, 2010)
I present five theses on the common within the context of the transformations of capitalist social relations as well as their contemporary global crisis. My framework involves “cognitive capitalism,” new processes of class composition, and the production of living knowledge and subjectivity. The commons is often discussed today in reference to the privatization and commodification of “common goods.” This suggests a naturalistic and conservative image of the common, unhooked from the relations of production. I distinguish between commons and the common: the first model is related to Karl Polanyi, the second to Karl Marx. As elaborated in the postoperaista debate, the common assumes an antagonistic double status: it is both the plane of the autonomy of living labor and it is subjected to capitalist “capture.” Consequently, what is at stake is not the conservation of “commons,” but rather the production of the common and its organization into new institutions that would take us beyond the exhausted dialectic between public and private.
Philosophy
Keywords: MARX; Karl; 1818-1883; Marxism; capitalism; class composition; cognitive capitalism; common; commons; financialization; model-based reasoning; operaismo; production (economic theory); subjectivity

Beyond Social Democracy? - Gare, Arran (International Journal of Inclusive Democracy, 2009)
Towards an Inclusive Democracy, it is argued, offers a powerful new interpretation of the history and destructive dynamics of the market and provides an inspiring new vision of the future in place of both neo-liberalism and existing forms of socialism. It is shown how this work synthesizes and develops Karl Polanyi's characterization of the relationship between society and the market and Cornelius Castoriadis' philosophy of autonomy. A central component of Fotopoulos' argument is that social democracy can provide no answer to neo-liberalism, so the only viable alternative to neo-liberalism is the form of inclusive democracy he elaborates. Reviewing Castoriadis' concept of autonomy, it is argued that while Fotopoulos is certainly correct given the present deformed nature of social democracy, there is no reason to exclude social democracy as such from what Fotopoulos calls the tradition of autonomy. It is suggested that if the working class movement could free itself from the capitalist imaginary and return to its quest for autonomy, a synthesis of a radically reformed social democracy and inclusive democracy could greatly improve the prospects of each to successfully challenge not only neo-liberalism, but also the emerging liberal fascism of USA, Britain and Australia.
Philosophy
Keywords: CASTORIADIS; Cornelius; 1922-1997; democracy; fascism; neoliberalism; political doctrines; political science - study & teaching; review; social democracy; social movements; socialism

Devons-nous mériter notre salaire ?, Do We Have To Deserve Our Salary ? - Girardot, Dominique (Revue du MAUSS, 2007)
L’idée qu’une rémunération juste du travail relève d’un calcul du mérite tend à s’imposer comme un lieu commun. Les présupposés et les conséquences d’une telle représentation sont ici interrogés dans la perspective ouverte par les analyses de Polanyi sur les effets dévastateurs de la fiction d’un marché autorégulateur lorsqu’elle atteint des réalités comme celles – parmi d’autres – du travail. Le paradigme du don et le concept arendtien de l’action permettent d’identifier, dans le besoin de reconnaissance, à la fois la source de l’efficacité de la fiction d’un mérite rétribuable et les raisons de son inévitable échec pratique. Non qu’on ne puisse instituer une rémunération au mérite ; mais c’est au prix d’une réification de l’activité humaine, lourde de menaces pour la réalité que nous partageons. ENG: The idea that a righteous work’s remuneration is to be measured by merit is tending to stand out as a commonplace. Presuppositions and consequences of such an idea are questioned here from Polanyi’s viewpoint on devastating effects of the selfregulating market’s fiction when realities as work are reached. The gift’s paradigm and Hannah Arendt’s concept of action allow to point out that the need of acknowledgement both gives its efficiency to the fiction of a payable merit and causes its inevitable practical failure. Not that it’s impossible to institute merit’s remuneration ; but it’s at the cost of reifying human activity, that threatens the reality we share.
Philosophy
Keywords: ARENDT; Hannah; payable merit; self-regulating market

Karl Polanyi, Marshall Sahlins, and the Study of Ancient Social Relations - Kirk, Alan (Journal of Biblical Literature, 2007)
Questions arise whenever social-scientific models are used in analysis of ancient texts, particularly regarding the feasibility of their application to social and cultural milieux different from those from which they were derived. An essay I authored that assessed the command in Luke 6 to "love your enemies" from the perspective of ancient reciprocity ethics, and that invoked Marshall Sahlins's taxonomy of reciprocity relations (general, balanced, and negative reciprocity), was queried by Zeba Crook on precisely this point, namely, whether it applied Sahlins's taxonomy to Greco-Roman reciprocity relations without adequate attention to the distinctions between kinship organized tribal societies (the focus of Sahlins's analysis) and the socially stratified agrarian societies characteristic of the ancient Mediterranean world.1 Crook's piece was more than just a critique on that point; it raised questions about the extent to which Sahlins's model has applicability to the Roman world. This essay will focus on this key point and, it is hoped, will also contribute to the discussion on the use of social-scientific research in biblical studies.
Religion Studies; Philosophy
Keywords: SAHLINS; Marshall; biblical studies; clientelism; cognitive models; economic models; kinship; reciprocity; slave trade; social interaction; stone age

Human Freedom and the 'Reality of Society': Origins and Development of Karl Polanyi's Ideas during the Interwar Period - Thomasberger, Claus (History of Economic Thought, 2005)
Karl Polanyi's most famous book, The Great Transformation, contains several ideas and theoretical notions which are at the heart of long-lasting controversies throughout the social sciences. Categories such as "double movement," "embeddedness," "disembedding," "market society," or "social freedom" have proved to be fruitful notions not only in anthropology, but also in sociology, political sciences, and economic history. The recent three volume publication of Karl Polanyi's writings during the interwar period–including published articles and unpublished manuscripts–opens for the first time the possibility to have a closer look at the origins and the development of some of Polanyi's concepts during the interwar period. In the paper titled "Human Freedom and the Reality of Society–Origins and Development of Karl Polanyi's Ideas during the Interwar Period," Claus Thomasberger addresses Polanyi's idea of a polar relationship between human freedom and the "reality of society." The paper offers new insights, discussing central questions which are crucial to the understanding of Polanyi's reasoning: Where are the roots of his central categories? What influence did Marx have on Polanyi's thinking? What is the relationship between Polanyi's approach and the Austrian School of Economics? Is it appropriate to read his work in terms of an institutional approach? In order to give an answer to these questions, the paper goes back not only to the 1930s, but to the 1920s as well. As it demonstrates, Polanyi had already developed the core ideas of his thinking in Vienna, participating actively in the discussions between the Austrian School of Economics and Austro-Marxism about the possibilities of a socialist society.
Economics; Philosophy
Keywords: history of economic thought: individuals; reality of society

Two heterodox economists: Neurath and Karl Polanyi - Giandomenica, Becchio (MyScienceWork Working paper No. 11/2005 Università di Torino 1, 2005)
This paper is based on the idea that between the 1920s and the mid-1930s in Vienna there were two forms of heterodox economic theory: the Austrian economic school headed by Ludwig von Mises and another interesting form of heterodox economics opposed to the Austrian school (above all politically) and pursued by various social thinkers (Otto Neurath, Karl Polanyi, Otto Bauer, Felix Schaffer, Felix Weil, Jacob Marschak). They were engaged in the debate on the possibilities of a planned economy: Austrian socialist economists proposed a sort of ‘third’ way between pure capitalism (whose Viennese stronghold was the Austrian economic school) and orthodox communism à la Kautzsky (deeply rooted in Germany). This paper focuses on the affinities between Neurath and Polanyi’s economic thought: despite some major differences between them, they shared a common philosophical background on which they founded their heterodox economic theory. After a brief historical premise, there is a first part, which deals with the debate on a planned economy and a second part, which deals with the influence of Neurath on the Polanyi’s vision of the faults of the neoclassical economic theory: the concepts of “disembedded economy” and of the so-called “economicistic fallacy”. NEURATH AND POLANYI IN VIENNA Neurath described himself as a ‘social engin
Economics; Philosophy
Keywords: Austrian economic school; NEURATH; Otto; economics; heterodox economics; philosophy; political science

Beyond Social Democracy? Takis Fotopoulos' Vision of an Inclusive Democracy as a New Liberatory Project - Gare, Arran (Democracy & Nature: The International Journal of Inclusive Democracy, 2003)
Towards an Inclusive Democracy, it is argued, offers a powerful new interpretation of the history and destructive dynamics of the market and provides an inspiring new vision of the future in place of both neo-liberalism and existing forms of socialism. It is shown how this work synthesizes and develops Karl Polanyi's characterization of the relationship between society and the market and Cornelius Castoriadis' philosophy of autonomy. A central component of Fotopoulos' argument is that social democracy can provide no answer to neo-liberalism, so the only viable alternative to neo-liberalism is the form of inclusive democracy he elaborates. Reviewing Castoriadis' concept of autonomy, it is argued that while Fotopoulos is certainly correct given the present deformed nature of social democracy, there is no reason to exclude social democracy as such from what Fotopoulos calls the tradition of autonomy. It is suggested that if the working class movement could free itself from the capitalist imaginary and return to its quest for autonomy, a synthesis or a radically reformed social democracy and inclusive democracy could greatly improve the prospects of each to successfully challenge not only neo-liberalism, but also the emerging liberal fascism of USA, Britain and Australia.
Philosophy
Keywords: FOTOPOULOS; Takis; autonomy (political science); democracy; liberalism; political science; socialism

Chapter 7: Karl Polanyi - Rogerson, Kenneth S.; May, Christopher (Key Thinkers for the Information Society, 2002)
This article presents Karl Polanyi's analysis of the dynamic relationships between economy and society in the information age. Of the many concepts Karl Polanyi provides in his analysis of economic relations, three stand as carefully calculated assumptions about the relationship between society and economy: the embeddedness of information in society, the commoditization of information and the existence of a double movement in the information revolution. Information has always been embedded in societal interactions. To emphasize this point, he said that the simple flow of information seems to have little effect in and of itself on the outcome of social interchanges. In Polanyi's words, it is also embedded in other social relations, such as political, economic, cultural, or health-related discussions and actions. On the issue of information commoditization, Polanyi takes a different view. His logic indicates that there will be negative social consequences associated with it. One example is digital divide or the discrepancies on a global or national level between those who have access to information through new technologies and those who do not. With regards to the existence of double movement, Polanyi believed that there are two opposing forces-economic liberalism and social protection-present during the industrial revolution. However, this is not easy to see in the information age because of simple paradox. First, people who would eschew the uses of technology for ideological reasons,may turn to it for other reasons. And second, there is only a protest of a specific issue and not the imbalance of information flows or the ownership of information dissemination methods.
Information Science; Philosophy; Communications
Keywords: commercialization; communication revolution; digital divide; industrial revolution; information technology; liberalism

A Tale of Three Karls: Marx, Popper, Polanyi and Post-Socialist Europe - Marquand, David (Royal Institute of Philosophy Supplement, 2000)
Focuses on the social and political changes brought about by capitalism in Europe. Advocacy of socialist Karl Marx, Karl Popper and Karl Polanyi for social democracy; Discussion on the relationship between society and economy; Notion of futurism regarding the inevitability of change.
Philosophy; Political Science
Keywords: Europe; European politics & government; capitalism; change; socialism

Capitalism and Crisis: Thinking Through Capitalist Crisis with Schumpeter and Polanyi - Delanty, Gerard (Capitalism, Democracy, Socialism: Critical Debates, 2022)
The chapter offers an analysis of capitalist crisis through a reading and discussion of two seminal texts on capitalism, Joseph Schumpeter’s Capitalism, Socialism and Democracy [1943] and Karl Polanyi’s The Great Transformation [1944]. These inspiring works on economic history and social theory offer profound insights into the nature of capitalist crisis. Although written in the mid-twentieth century many of the insights in these books are of relevance to the current situation as capitalism undergoes another revulsion. While the two authors were very different – Polanyi a left-wing critic of capitalism; Schumpeter a politically right-wing economist who favoured capitalism – both were influenced by Marx’s analysis of capitalism and have helped to shape the debate on the crisis of capitalism. Indeed, Schumpeter was convinced Marx was mostly right in his prediction of the end of capitalism and the triumph of socialism. The chapter begins with a brief account of the Marxist theory capitalism in order to contextualise the discussion of the two theorists.
Political Science; Philosophy
Keywords: MARX; Karl; 1818-1883; Polanyi; SCHUMPETER; Joseph Alois; 1883-1950; capitalism; crisis

¿Uno de los nuestros?: otra vuelta de tuerca al marxismo de Karl Polanyi - Rodríguez, Sergio Braulio Véliz (El Buho: Revista electrónica de la Asociación Andaluza de Filosofía, 2022)
Este ensayo trata de situar la obra de Karl Polanyi en la tradición del pensamiento marxista heterodoxo, respondiendo a las objeciones que se han planteado en contra de tal filiación. Se analizan para ello los conceptos fundamentales del pensamiento del autor desde un punto de vista marxista: la “economía sustantiva” y la “economía formal”, la “falacia economicista”, la “incrustación” (Embeddedness) de la economía, las “mercancías ficticias” y el “doble movimiento”.
Philosophy
Keywords: Marxism; double movement; economi; economistic fallacy; embeddedness; embeddness; fictitious commodities; formal economy; substantive economy

Società, mercato, libertà. Karl Polanyi e Friedrich von Hayek - BIONDI, NICCOLO (2021)
La riflessione di Karl Polanyi e Friedrich August von Hayek consente di analizzare da due punti di vista molto diversi la metodologia delle scienze sociali, la teoria adatta a studiare l'attività economica, l'organizzazione economica capitalistica e la società di mercato, le cause e il significato dei totalitarismi, il significato della libertà in una società complessa.
Philsophy
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; capitalism; markets

Wirtschaftsethik der ›always embedded market economy‹. Überlegungen zu einer Idee von Polanyi - Haase, Michaela (Zeitschrift für Wirtschafts- und Unternehmensethik, 2021)
Capitalism is a social relation that cannot be reduced to the characteristics associated with it - markets, private property, profit and profit orientation. This relation can be shaped in different ways. The article refers to Karl Polanyi’s idea of the ›always embedded market economy‹ in order to develop basic characteristics of an example of post-capitalist economic ethics. Alternate abstract: Der Kapitalismus ist ein soziales Verhältnis, das sich nicht auf die mit ihm in Verbindung gebrachten Merkmale - Märkte, Privateigentum, Gewinn- und Profitorientierung - reduzieren lässt. Dieses Verhältnis kann auf verschiedene Weise ausgestaltet werden. Der Beitrag referiert auf die Idee der ›always embedded market economy‹ von Karl Polanyi, um Grundzüge einer postkapitalistischen Wirtschaftsethik zu entwickeln.
Economics; Philosophy
Keywords: business and economics; capitalism; ethics; market economies; philosophy; private property

Karl Polanyi and the Contemporary Political Crisis: Transforming Market Society in the Era of Climate Change - Kirby, Peadar (Bloomsbury Publishing, 2020)
Has politics reached breaking point? Rather than defending liberalism or abandoning it, how can a socially just and ecological alternative be built? Peadar Kirby investigates the causes of our current multifaceted global crisis by drawing on the work of Karl Polanyi. This book explores Polanyi's theory that social disruptions result from the attempt to run society according to the rules of the market. Drawing on these ideas, it outlines pathways towards an alternative future that overcome weaknesses in Marxism. Linking the ecological, political and socio-economic crises, Kirby identifies that an alternative socio-ecological model is emerging, consistent with the insights of Polanyi. Karl Polanyi and the Contemporary Political Crisis is an urgent intervention into key debates on the future of politics, on the low-carbon transition, on automation and on the emerging world order.
Keywords: climate change; ecological crisis

Capitalismo e lutas sociais: abordagens recentes à articulação entre Marx e Polanyi - Filho, Ricardo Framil (Cadernos CERU, 2020)
The article explores recent contributions that rely on the combination of ideas from Karl Marx and Karl Polanyi to conceptualize social struggles. Two approaches are presented: selective perspectives, which highlighted the differences between class struggles as defined by the Marxist tradition and social reactions theorized by Karl Polanyi’s double movement, and inclusive viewpoints, that emphasized the potential convergence between these different expressions of contestation. Thus, we seek the basic elements of a theory of the structural roots of social struggles in contemporary capitalism. Thereafter, the article explores with greater attention the theories of Michael Burawoy and Nancy Fraser. A comparative reading indicates that this theoretical project is promising because it allows for social struggles to be linked to systemic contradictions, but it also shows that relevant conceptual difficulties persist. The conclusion is that more than a definitive theory, the debates raised by this theoretical outlook suggest central questions for the reflection on labor, classes and capitalist societies at large. O artigo explora contribuições recentes que propuseram a articulação teórica entre ideias de Karl Marx e de Karl Polanyi para conceptualizar as lutas sociais. São identificadas duas abordagens: perspectivas seletivas, que destacaram as diferenças entre as lutas de classes tal como definidas pela tradição marxista e as reações sociais teorizadas pela tese do duplo movimento de Karl Polanyi, e sínteses ecléticas, que enfatizaram a convergência potencial entre essas diferentes expressões de contestação social. Buscam-se, assim, os elementos fundamentais de uma teoria das raízes estruturais das lutas sociais no capitalismo contemporâneo. Explora-se com maior cuidado, então, as teorias de Michael Burawoy e de Nancy Fraser. Uma leitura comparativa indica que essa orientação teórica é promissora porque permite associar as lutas sociais a contradições sistêmicas, mas revela, também, que persistem dificuldades conceituais relevantes. Conclui-se que mais do que uma teoria definitiva, os debates suscitados por essa vertente teórica sugerem questões centrais para a reflexão sobre o trabalho, as classes e as sociedades capitalistas em um sentido amplo.
Philosophy
Keywords: MARX; Karl; 1818-1883; capitalismo; duplo movimento; lutas de classes; lutas sociais

The Belief in Economic Determinism, Neoliberalism, and the Significance of Polanyi's Contribution in the Twenty-First Century - Thomasberger, Claus (International Journal of Political Economy, 2012)
How can we explain why Karl Polanyi's book The Great Transformation is more relevant today than ever before? The central thesis of the paper is that Polanyi's analysis is groundbreaking because it goes far beyond the interpretation of the civilization of the nineteenth century. By focusing on the "belief of economic determinism," Polanyi challenges the juxtaposition of being and thinking, of material life-process and consciousness. He rejects the assumption that society encompasses a world of objective facts independent of theoretical beliefs and visions. Polanyi's work is of utmost importance today because by anticipating a change in approach such as the liberal authors made, from the opposite point of view, during the interwar period, he offers the key not only to the analysis of the market mechanism, but also to a critical understanding of neoliberalism.
Economics; Philosophy
Keywords: Austrian school; Austrian school of economics; Great Transformation; The (Book); Keynesian economics; Marxist philosophy; POLANYI; Karl; 1886-1964; belief & doubt - social aspects; central economic planning - social aspects; double movement; economic determinism; economic history - 19th century; economic planning; economic theory; fictitious commodities; free enterprise - social aspects; history of economics - 20th century; human behavior - economic aspects; laissez-faire; neoliberalism; neoliberalism - social aspects; self-fulfilling prophecy; socioeconomics; utopias - economic aspects

'Planning for Freedom': Hayekian and Polanyian Policies in Latin America - Valderrama, Paula (International Journal of Political Economy, 2012)
In the first part of the paper, the concepts of "planning for freedom" by Friedrich Hayek and Karl Polanyi are compared. Hayek rejects "central planning" and also all kinds of "planning for specific aims," but he defends the principle of "planning for competition" as the main condition of a free society. This principle includes the provision of a pertinent institutional framework and state intervention to create markets in spheres of society previously ruled by nonmarket principles. Polanyi agrees that "planning" is necessary in order to achieve freedom in a complex society, but he criticizes the liberal understanding of freedom as a vain "illusion" and considers the principle of "planning for competition" a political ideal that endangers the cohesion of societies. The starting point of Polanyi's argumentation is Karl Marx's theory of reification, but he goes beyond this, complementing it with the concept of "social freedom" based on knowledge and responsibility. Considering the Latin American experience in recent decades, the paper compares Hayekian and Polanyian concepts of "planning for freedom" in their real political and social dimensions.
Philosophy; Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Latin America; capitalist systems: planning; coordination; and reform; formal and informal sectors; freedom; history of economic thought: individuals; institutional arrangements; planning models; planning policy; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; shadow economy